2005
DOI: 10.1016/j.clim.2005.06.015
|View full text |Cite
|
Sign up to set email alerts
|

T cell subset and cytokine profiles in human visceral leishmaniasis during active and asymptomatic or sub-clinical infection with Leishmania donovani

Abstract: During an epidemiological study of visceral leishmaniasis (VL) in south-west Ethiopia, 33 VL patients, 9 treated VL patients, 14 individuals with sub-clinical infection, 34 individuals with asymptomatic infection, and 19 healthy controls were studied for T cell subsets and cytokine profiles. Negative leishmanin skin test, CD3 and CD4 lymphocytopenia, and significantly reduced numbers of memory CD4+ T cells were found in VL patients compared to treated VL patients or persons with self-limiting asymptomatic infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
62
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 44 publications
(38 reference statements)
8
62
0
1
Order By: Relevance
“…IL-12 also plays a key role in the initiation and maintenance of Th1 responses and the subsequent production of IFN-γ (Ghalib et al 1995). However, studies using the sera of patients with VL from Iran (Khoshdel et al 2009), southeast Ethiopia (Hailu et al 2005) and Brazil (Caldas et al 2005) have shown significantly higher levels of IL-12 in patients with the active disease relative to those in asymptomatic and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 also plays a key role in the initiation and maintenance of Th1 responses and the subsequent production of IFN-γ (Ghalib et al 1995). However, studies using the sera of patients with VL from Iran (Khoshdel et al 2009), southeast Ethiopia (Hailu et al 2005) and Brazil (Caldas et al 2005) have shown significantly higher levels of IL-12 in patients with the active disease relative to those in asymptomatic and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies evaluating cytokines in serum samples have either not detected or found low concentrations of 69,70 , other studies have produced conflicting results. IFN-g was detected in 17 of 44 patients in Iran 2 and in 13 of 15 patients in Brazil 20 ; in addition, high levels have been confirmed in patients in Asia, Europe, Africa, and Brazil 9,15,31,32,50,52 . These differing results are most likely not related to the selected patient groups or to the Leishmania species involved, but rather to the samples that were analyzed.…”
mentioning
confidence: 87%
“…Therefore, PBMCs would consist of a non-Leishmania antigen-specific population, which would fail to proliferate or produce cytokines upon Leishmania antigen stimulation. It is also possible that the PBMCs are pre-activated and cannot be further stimulated; this is less likely, however, since a study in Ethiopia compared individuals with active disease, cured disease, subclinical manifestations, asymptomatic disease, and no disease and found that memory (CD45RO + CD27 + ) CD4 + cells and naïve (CD45RO -CD27 + ) CD8 + cells were at their lowest levels in patients with the active disease 31 . Furthermore, the same study found that phorphol miristate acetate-and ionomycin-induced CD4 + and CD8 + cell IFN-g production was at its lowest level in patients with the active disease 31 .…”
Section: Immunoactivation In Lymphoid Organsmentioning
confidence: 99%
“…is critically mediated by gamma interferon (IFN-␥)-producing Th1 cells, which activate macrophages to produce leishmanicidal compounds, such as nitric oxide (NO) (2). Together with IFN-␥, the inflammatory cytokine interleukin-17A (IL-17A) also mediates protection against L. infantum (3,4). On the other hand, Th2 cytokines are involved in susceptibility to leishmaniasis (2,5).…”
mentioning
confidence: 99%